Cascade screening based on genetic testing is cost-effective: Evidence for the implementation of models of care for familial hypercholesterolemia - Ademi, Z.; Watts, G.; Pang, J.; Sijbrands, E.; Van Bockxmeer, F.; O'Leary, Peter; Geelhoed, E.; Liew, D. (Elsevier, 2014)
Background: Familial hypercholesterolemia (FH) imposes significant burden of premature coronary heart disease (CHD). Objective: This study aimed to determine the cost-effectiveness of FH detection based on genetic testing, supplemented with the measurement of plasma low-density lipoprotein cholesterol concentration, and treatment with statins. Methods: A Markov model with a 10-year time horizon was constructed to simulate the onset of first-ever CHD and death in close relatives of probands with genetically confirmed FH. The model comprised of 3 health states: “alive without CHD,” “alive with CHD,” and “dead.” Decision-analysis compared the clinical consequences and costs of cascade-screening vs no-screening from an Australian health care perspective. The annual risk of CHD and benefits of treatment was estimated from a cohort study. The underlying prevalence of FH, sensitivity, specificity, cost of screening, treatment, and clinic follow-up visits were derived from a cascade screening service for FH in Western Australia. An annual discount rate of 5% was applied to costs and benefits. Results: The model estimated that screening for FH would reduce the 10-year incidence of CHD from 50.0% to 25.0% among people with FH. Of every 100 people screened, there was an overall gain of 24.95 life-years and 29.07 quality-adjusted life years (discounted). The incremental cost-effectiveness ratio was in Australian dollars, $4155 per years of life saved and $3565 per quality-adjusted life years gained. Conclusion: This analysis within an Australian context, demonstrates that cascade screening for FH, using genetic testing supplemented with the measurement of plasma low-density lipoprotein cholesterol concentrations and treatment with statins, is a cost-effective means of preventing CHD in families at risk of FH.